Unraveling the deformation behavior of the Fe45Co25Ni10V20 high entropy alloy. (June 2023) - Li, Y.X.; Nutor, Raymond Kwesi; Zhao, Q.K.; Zhang, X.P.; Cao, Q.P.; Sohn, S.S.; Wang, X.D.; Ding, S.Q.; Zhang, D.X.; Zhou, H.F.; Wang, J.W.; Jiang, J.Z.
Highlights: The novel Fe45 Co25 Ni10 V20 high-entropy alloy displays excellent tensile properties at ambient and cryogenic temperatures. The deformation-induced BCC nucleation occurs at grain boundaries and stacking fault intersections to contribute to the strain hardening of the alloy. The onset of FCC→BCC martensitic transformation at 77 K induces a Lüders-like deformation with Lüders strain of up to 35% delaying macroscopic necking. The deformation substructures of dislocations, stacking faults, and bcc martensite are further confirmed by Monte Carlo (MC) and molecular dynamics (MD) simulations. Abstract: Here we report on the tensile deformation behavior of a face-centered cubic (FCC)-structured Fe45 Co25 Ni10 V20 high-entropy alloy at cryogenic temperature (77 K). The alloy displays an impressive 1.1 GPa tensile strength while maintaining an ultrahigh fracture elongation of 82% with a minimum strain hardening rate at a true strain of about 40%. We elucidate such unique mechanical properties, originating from the strain-induced FCC to body-centered cubic (BCC) martensitic transformation, where the high-stress concentrations at grain boundaries or intersection of stacking faults can stimulate phase transition. The martensitic transformation can induce strain softening by consuming the stored deformation energy while contributing to the strain hardening via the transformation itself and further deformation of BCC phases. Such a dynamic balance between softening and hardening enables a relatively uniform plastic flow, resulting in a plastic deformation with a strain range of up to 35% delaying macroscopic necking. The findings provide further insights into the significance of transformation-induced plasticity effects on the cryogenic performance of alloys. Graphical abstract: Image, graphical abstract